Falls and Fractures among Nursing Home Residents Treated with Pimavanserin versus Other Atypical Antipsychotics: Analysis of Medicare Beneficiaries with Parkinson's Disease Psychosis - Krithika Rajagopalan; Nazia Rashid; Daksha Gopal; Dilesh Doshi (Adis, Springer Healthcare, 2024)
Abstract Background Reducing falls and fractures remains an important clinical goal in managing older residents with Parkinson's disease psychosis (PDP) in long-term care/nursing home (LTC/NH) settings. Objectives This analysis examined risk of all-cause falls or fractures among PDP residents on continuous monotherapy with pimavanserin (PIM) versus (i) other atypical antipsychotics (AAPs) [quetiapine (QUE), risperidone (RIS), olanzapine (OLA), aripiprazole (ARI)] and (ii) QUE. Methods A retrospective analysis of parts A, B, and D claims from a 100% Medicare sample (2013-2019) in LTC/NH settings was conducted. LTC/NH residents in the USA initiating continuous monotherapy (PIM versus other AAPs; PIM versus QUE) for ≥ 6 months between 01 January 2014 and 31 December 2018 were 1:1 propensity score matched (PSM) on 31 variables (age, sex, race, region, and 27 Elixhauser comorbidities). Outcomes included three measures: risks of falls only, fractures only, and falls/fractures during 6-months follow-up. Demographic characteristics were described using chi-square and t-tests. Generalized linear models were used to assess difference in risks of falls/fractures. Results Of 7187 residents, 47.59% (n = 3420) were female and mean age was 78.8 (± 7.75) years. In total, 14% (n = 1005) were on PIM and 86% (n = 6182) were on other AAPs. After PSM, falls only among PIM residents (n = 1005) was 4.58% (n = 46) versus 7.66% (n = 77) for other AAPs (n = 1005) [relative risk (RR) = 0.63 (0.46, 0.86), p < 0.05] and 8.26% (n = 83) for QUE (n = 1005) residents (p < 0.05). Fractures only among PIM residents was 1.39% (n = 14) compared with 2.09% (n = 21) for other AAPs (p = 0.31) and 1.89% (n = 19) for QUE (p = 0.49), respectively. Taken together, falls/fractures among PIM residents were 5.67% (n = 57) versus 9.05% (n = 91) for other AAPs [RR = 0.63 (0.46, 0.86), p < 0.05] and 9.55% (n = 96) for QUE (p < 0.05), respectively. Conclusions In this analysis of LTC/NH residents with PDP, PIM had a 37% and 41% lower risk of all-cause falls/fractures versus other AAPs and versus QUE, respectively.